Matching frictions, efficiency wages, and unemployment in the USA and the UK - James M. Malcomson; Sophocles Mavroeidis (Brown University, Department of Economics, 2007)
This paper combines matching frictions with e ciency wages to deter shirking in a model that is estimated for the USA and the UK to derive the underlying structural parameters. Methods robust to weak instruments are used to show that, for both countries, both matching frictions and efficiency wages play a significant role in enabling the model to fit the data even with non-prescriptive formulations for wage determination. The results indicate that adding an efficiency wage element to matching frictions may be a better way to fit the data than simply searching for an alternative wage formulation.
Keywords: E2; J3; J6; 330; Matching frictions; efficiency wages; unemployment; shirking; robust inference; Arbeitsmarkttheorie; Effizienzlohn; Arbeitslosigkeit; Lohnbildung; Großbritannien; USA